Prevalence and consequences of bovine subclinical mastitis in hill tract areas of the Chattogram division, Bangladesh - Md. Piplu Mia; Hemayet Hossain; Khadiza Akter Brishty; Md. Shahidur Rahman Chowdhury; Md. Imranuzzaman; Mostafizor Rahman; Sadia Islam Ria; Milon Mia; Md Saidul Haque; Md. Ashik-uz-zaman; Md. Nazmul Haque; Anzuman Ara; et al. (Journal of Advanced Biotechnology and Experimental Therapeutics)
Mastitis is a common problem in Bangladeshi dairy cattle production. This study investigated the prevalence of subclinical mastitis (SCM), its impact on milk production and reproduction, and the resultant economic losses among dairy farms in the Chattogram division, Bangladesh. A cross-sectional study evaluated 161 farms, collecting 4,048 quarter milk samples from 1,012 cows to conduct a primary screening for SCM using the California mastitis test (CMT). Additional surveys were conducted on SCM-positive farms and animals to explore production and economic impacts. The prevalence of SCM at the farm level was 76.8% (43/56) in Chattogram and 69.5% (73/105) in Cox's Bazar. At the quarter level, the prevalence of SCM was found to be 32.29% (1307/4048; 95% CI: 30.9-33.8), while at the animal level, it was 41.3% (418/1012; 95% CI: 38.3-44.4). Crossbred cows exhibited a higher susceptibility to SCM at 47.2%, compared to indigenous breeds (31.2%). SCM significantly (p [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 163-181]